Picturing, Pledges and Other Scripted Acts: Performance (In) Art - Dave Beech (Arts, 2023)
This essay re-examines several examples of non-performance based artworks from the perspective and history of performance art. For instance, the photomontages I produced as an undergrad art student were based on repeated acts of stealing posters from their public sites on the street between my house and the college. Later, while working collaboratively with Mark Hutchinson in Manchester and London, we made photograms and paintings of scenes that we enacted on the street (striking a match, taking a flag for a walk). Years later, as a solo artist again, I produced a body of work in the form of slide presentations that consisted of photographs of me dressed in homemade costumes that cast me as a monster. In my work with the Freee art collective, we used slogans, our own bodies, costumes and props to give material reality to slogans that we treated as scripts. We wrote manifestos and staged events in which participants read. So, while the forms of my work are image based, the rationale is typically tied to the techniques and values of performance.